Molecular Cloning, Expression and FPLC Purification of Lectin A from Pseudomonas aeruginosa - Ghoraishizadeh, Peyman; Raikar, Shraddha; Takhtechian, Mahsa (International Journal of Applied Sciences and Biotechnology, 2014)
Pseudomonas aeruginosa (PA) as an opportunistic pathogen infects the pulmonary tract, bladder, cystic fibrosis patients and burn victims. PA infections treatment is challenging because of its ability to rapidly develop resistance to multiple classes of antibiotics. Lectin is protein that isexpressed in cell of PA and cause of infection by attaching to the host cells. Lectin A gene coding lectin protein so we cloned and expressedthis gene then purified of related protein, that can be used in preparation of vaccine to treat PA infections. DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11559 Int J Appl Sci Biotechnol, Vol. 2(4): 529-536